Participatory Design of Interactive Computer-Based Learning Systems - Zaphiris, Panayiotis; Zacharia, Giorgos (My University, 2005)
We present an iterative evaluation methodology (as part of a participatory design methodology) employed in an online course for learning Modern Greek. Unlike other educational technology evaluation methodologies that focus primarily on questionnaires that administer summative and formative evaluation methods (Kandaswamy, 1990; Scriven, 1980), we propose a hybrid evaluation that is unique in the following ways. 1. It becomes an integral part of all stages of our design methodology, so every stage of the development is based on user feedback and evaluation. 2. In addition to evaluation questionnaires, we also collected feedback from our users through our interaction with the students during our collaborative design and development of the course. The students contributed lecture notes, quizzes, and student diaries that enabled us to evaluate the pedagogical value of our course, ensuring continuous feedback from the students regarding the usability and adequacy of the course.